Space stations and beyond - Hamilton, John, 1959- (Minneapolis, Minnesota : Abdo & Daughters, an imprint of Abdo Publishing, 2019)
The cost of the Space Race for both the United States and the Soviet Union was immense, but many technology advancements resulted, including satellite communications and GPS navigation. With so much invested, both countries continued their space exploration efforts, even cooperating on some projects, such as the International Space Station. This title examines the Skylab and Mir space stations, both nations' space shuttle efforts, and space exploration probes, leading to today's international cooperation between space agencies of the United States, Russia, Europe, and others.
Beyond the space race -- Salyut space stations -- Soyuz spacecraft -- Soyuz 11 tragedy -- Skylab -- Apollo-Soyuz Test Project -- Space shuttle -- The Challenger and Columbia tragedies -- Mir Space Station -- International Space Station -- Future space stations -- Timeline.
Includes index.
Ages 8-12.
109562
Keywords: Space stations -- Juvenile literature; Space race; Space race; Space stations; Juvenile works -- non-fiction.